Food choices of the young minds: a study among adolescents in urban slum area of Ludhiana - Singh, Arshdeep; Girdhar, Sangeeta; Gupta, Vikram Kumar; Chaudhary, Anurag (International Journal Of Community Medicine And Public Health, 2026)
Background: Adolescence is a critical period of growth during which dietary habits strongly influence health and nutritional status. Unhealthy eating practices contribute to both undernutrition and overweight/obesity among adolescents. This study assessed the dietary habits and nutritional status of adolescents in an urban slum area of Ludhiana. Methods: A cross-sectional study was conducted among adolescents in an urban slum area of Ludhiana. Data on dietary habits were collected using a pretested questionnaire and anthropometric measurements were recorded to assess their nutritional status. Results: Among 202 adolescents, 51.5% were girls and the mean age was 14.99±1.09 years. Overall, 50.0% had normal BMI, 37.6% were thin and 12.4% were overweight/obese. Thinness was significantly higher among boys (48.0%) than girls (27.9%), while girls had a higher prevalence of normal BMI (61.5%) (p=0.003). More than half (52.0%) of the adolescents skipped breakfast, with significantly higher prevalence among girls (p=0.001). Junk food consumption was reported by 84.2% and carbonated drink intake by 68.3% of participants. Fruit and vegetable intake was higher among younger adolescents (p=0.043), while carbonated drink consumption increased with age (p=0.016). Conclusions: Unhealthy dietary habits, particularly junk food consumption and breakfast skipping, were common among adolescents. These behaviors may contribute to malnutrition and future health risks. School-based nutrition education and healthy food policies are needed to encourage healthier dietary practices.